Communicating Science: Insights from Indonesian Higher Education Institutions - Eko Prasetyo Nugroho Saputro; Ismi Dwi Astuti Nurhaeni; Andre N. Rahmanto; Sri Hastjarjo (Proceedings Series on Social Sciences & Humanities, 2025)
This study investigates science communication processes at Universitas Indonesia (UI), Universitas Gadjah Mada (UGM), and Institut Teknologi Bandung (ITB) using a qualitative multiple case study design. Data were collected through in-depth interviews and document analysis, involving 15 key informants. Analysis employed an explanation-building approach in three stages—data collection, case profiling, and conclusion formulation—supported by triangulation through data cross-checking, member checks, and expert consultations to enhance reliability. Findings show that science communication in these universities forms an ecosystem that integrates communicators, messages, media, receivers, and feedback. Institutional actors act as strategic intermediaries, translating scientific knowledge into accessible, actionable forms. Messages align with national and global priorities and are tailored to audience needs. Communication channels combine formal academic outlets with digital media, public events, and community engagement, ensuring broad reach. Receivers—ranging from policymakers and industry to grassroots communities—participate actively, fostering two-way knowledge exchange and collaborative problem-solving. Feedback loops from internal teams and external stakeholders refine both research and its dissemination. Overall, the study highlights a holistic and impact-oriented framework for science communication in Indonesian higher education, bridging academia, industry, policymakers, and the public. This model strengthens national science communication capacity and offers a replicable strategy for linking research with societal needs.